CoN5 Sites Constructed by Anchoring Co Porphyrins on Vinylene‐Linked Covalent Organic Frameworks for Electroreduction of Carbon Dioxide - Zhai, Lipeng; Yang, Shuai; Lu, Chenbao; Cui, Cheng‐Xing; Xu, Qing; Liu, Jing; Yang, Xiubei; Meng, Xutong; Lu, Siyu; Zhuang, Xiaodong; Zeng, Gaofeng; Jiang, Zheng (Small (Weinheim an der Bergstrasse, Germany), 2022)
Developing effective electrocatalysts for CO2 reduction (CO2RR) is of critical importance for producing carbon‐neutral fuels. Covalent organic frameworks (COFs) are an ideal platform for constructing catalysts toward CO2RR, because of their controllable skeletons and ordered pores. However, most of these COFs are synthesized from Co‐porphyrins or phthalocyanines‐based monomers, and the available building units and resulting catalytic centers in COFs are still limited. Herein, Co‐N5 sites are first developed through anchoring Co porphyrins on an olefin‐linked COF, where the Co active sites are uniformly distributed in the hexagonal networks. The strong electronic coupling between Co porphyrins and COF is disclosed by various characterizations such as X‐ray absorption spectroscopy (XAS) and density functional theory calculation (DFT). Thanks to the CoN5 sites, the catalytic COF shows remarkable catalytic activity with Faraday efficiencies (FECO) of 84.2–94.3% at applied potentials between −0.50 and −0.80 V (vs RHE), and achieves a turnover frequency of 4578 h–1 at −1.0 V. Moreover, the theoretical calculation further reveals that the CoN5 sites enable a decrease in the overpotential for the formation COOH*. This work provides a design strategy to employ COFs as scaffold for fabricating efficient CO2 electrocatalysts. An olefin‐linked covalent organic framework (COF) with abundant cyano groups is constructed and developed as a scaffold of Co porphyrin (CoPor) to construct Co‐N5 sites for the electrochemical CO2 reduction reaction (CO2RR). The COF@CoPor exhibits unprecedented electrocatalytic performance in terms of catalytic activity and selectivity for CO2RR owing to strong electronic coupling between isolated CoPor and COF, large surface area, and highly exposed active sites.